1986
DOI: 10.1037/0022-006x.54.4.416
|View full text |Cite
|
Sign up to set email alerts
|

Social support as coping assistance.

Abstract: It is useful to reconceptualize social support as coping assistance. If the same coping strategies used by individuals in response to stress are those that are applied to distressed persons as assistance, models of coping and support can be integrated. To illustrate the utility of such an integration, coping strategies and support strategies are derived from a more general theory of stress-buffering processes in this article. A variety of supportive strategies not previously identified by researchers are deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

54
913
4
44

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,345 publications
(1,015 citation statements)
references
References 34 publications
(66 reference statements)
54
913
4
44
Order By: Relevance
“…Lazarus (1991) differentiates problemfocused from emotion-focused coping. Instrumental support and problem-focused coping are both directed at managing a stressful situation, whereas emotional support and emotion-focused coping are directed at relieving negative emotions during a stressful situation (Thoits 1986). In particular, proactive coping-the active endeavour to improve one's life-was found to be negatively associated with depression (Greenglass et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lazarus (1991) differentiates problemfocused from emotion-focused coping. Instrumental support and problem-focused coping are both directed at managing a stressful situation, whereas emotional support and emotion-focused coping are directed at relieving negative emotions during a stressful situation (Thoits 1986). In particular, proactive coping-the active endeavour to improve one's life-was found to be negatively associated with depression (Greenglass et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, proactive coping-the active endeavour to improve one's life-was found to be negatively associated with depression (Greenglass et al 2006). Thus, accepting Thoits' (1986) definition of social support as coping assistance, the providers of social support help the receiver cope successfully with stressful situations, which in turn decreases the risk of a depressive reaction. This is in line with the findings of Greenglass (1993), who found an association between social support and proactive coping.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, individuals working in the caring professions often attempt to alter the behaviors and emotions of their clients by providing emotional support (e.g., empathy), strategies for coping with emotions, or better cognitive management skills (Boscarino, 1997;Francis, 1997;Thoits, 1986). Within the context of formal caregiving, providing therapy to clients who have survived a traumatic event can be particularly stressful (Figley, 1995 (Figley, 1995;Nelson-Gardell & Harris, 2003;Schauben & Frazier, 1995).…”
Section: Abstract Compassion Fatigue; Secondary Trauma; Occupationalmentioning
confidence: 99%
“…Studies have shown that providing such care can be both highly rewarding and highly stressful (Ohaeri, 2003). Individuals working in the caring professions, though, may have occupational environments and caregiving demands that increase the likelihood of adverse psychological outcomes (Figley, 2002a;Sabin-Farrell & Turpin, 2003).Theoretically, individuals working in the caring professions often attempt to alter the behaviors and emotions of their clients by providing emotional support (e.g., empathy), strategies for coping with emotions, or better cognitive management skills (Boscarino, 1997;Francis, 1997;Thoits, 1986). Within the context of formal caregiving, providing therapy to clients who have survived a traumatic event can be particularly stressful (Figley, 1995 (Figley, 1995;Nelson-Gardell & Harris, 2003;Schauben & Frazier, 1995).…”
mentioning
confidence: 99%
“…Research in the general population has found that social support can act as a source of "assistance" in coping with stress (Thoits, 1986). However, only one published study has investigated the relationship between social support and coping among people with schizophrenia (MacDonald, Pica, McDonald, Hayes, & Baglioni, 1998).…”
Section: Enduring Environmental Conditions and Copingmentioning
confidence: 99%